2017
DOI: 10.21815/jde.016.010
|View full text |Cite
|
Sign up to set email alerts
|

Dental Students’ Clinical Experience Across Three Successive Curricula at One U.S. Dental School

Abstract: As dental schools continue to seek the most effective ways to provide clinical education for students, it is important to track the effects innovations have on students’ clinical experience to allow for quantitative comparisons of various curricula. The aim of this study was to compare the impact of three successive clinical curricula on students’ experience at one U.S. dental school. The three were a discipline‐based curriculum (DBC), a comprehensive care curriculum (CCC), and a procedural requirement curricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…The development processes of identified systems were evaluated in light of Kane's views of validity 21 . Of these, 3 studies used insurance‐based RUVs to measure students’ performance, 1,16,17 and 5 described systems that were specifically developed for the educational setting 5–7,18,19 . Alignment between the purpose of developing the RUV system and the purpose it was used for, was noted in 2 of the 8 systems 6,7 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The development processes of identified systems were evaluated in light of Kane's views of validity 21 . Of these, 3 studies used insurance‐based RUVs to measure students’ performance, 1,16,17 and 5 described systems that were specifically developed for the educational setting 5–7,18,19 . Alignment between the purpose of developing the RUV system and the purpose it was used for, was noted in 2 of the 8 systems 6,7 .…”
Section: Resultsmentioning
confidence: 99%
“…However, justification of the basis of calculation was provided by 1 study only 7 . Three published systems mentioned involvement of faculty members in the development process 5,7,18 ; however, detailed reporting of how validity was established was not provided. For instance, 1 study identified having “a reasonably organized and efficient dental student should earn roughly 6 CEUs per hour of patient treatment, as a rule of thumb 19 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations